PENGARUH AKUNTABILITAS, DUE PROFESSIONAL CARE,PERILAKU DISFUNGSIONAL DAN TIME BUDGETPRESSURE TERHADAP KUALITAS AUDITPADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA MEDAN: PENGARUH AKUNTABILITAS, DUE PROFESSIONAL CARE,PERILAKU DISFUNGSIONAL DAN TIME BUDGETPRESSURE TERHADAP KUALITAS AUDITPADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA MEDAN - Umeir Ramadani; Japrandi Pranata Sitepu (Institute of Computer Science (IOCS), 2019)
This research aim to test weather accountability, due profesional care, disfunctional act, and time budget pressure effect the audit quality. The population in this study were all auditors working at the Public Accountant Office in the city of Medan. The total sample used in this study were 70 auditors by using nonprobability sampling technique. The data source in this study is primary data. Data collection techniques using survey or questionnaire. Data analysis method used multiple linear regression analysis with the help of SPSS application. The result showed that in simultaneously accountability, due professional care, dysfunctional actand time budget pressure had a significant effect toward the audit quality. In partially accountability, due professional care, dysfunctional act and time budget pressure had a significant effect toward the audit quality. Meanwhile dysfunctional act and time budget pressure affect negatively and significant toward the audit quality.